2005
DOI: 10.1212/01.wnl.0000158476.74580.a8
|View full text |Cite
|
Sign up to set email alerts
|

Executive dysfunction in hyperhomocystinemia responds to homocysteine-lowering treatment

Abstract: An elevated serum homocysteine level is a risk factor for the development of cognitive impairment. Reported is a late-onset case of hyperhomocystinemia due to a vitamin B12 metabolic deficit (cobalamin C) with cognitive impairment, primarily in frontal/executive function. After homocysteine-lowering therapy, the patient's functional and neuropsychological status improved in conjunction with a decrease in leukoariosis on his MRI scan. These findings suggest that homocysteine-related cognitive impairment may be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 12 publications
2
25
0
Order By: Relevance
“…At this time, the patient continues to have sequelae from the vascular accident. Review of the literature suggests that early initiation of treatment could reverse the neurological and psychiatric symptoms at least partially [Shinnar and Singer, 1984;Kazimiroff and Shaner, 1991;AugoustidesSavvopoulou et al, 1999;Bodamer et al, 2001;Roze et al, 2003;Boxer et al, 2005] (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…At this time, the patient continues to have sequelae from the vascular accident. Review of the literature suggests that early initiation of treatment could reverse the neurological and psychiatric symptoms at least partially [Shinnar and Singer, 1984;Kazimiroff and Shaner, 1991;AugoustidesSavvopoulou et al, 1999;Bodamer et al, 2001;Roze et al, 2003;Boxer et al, 2005] (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that elevated serum levels increase the risk for neurodegenerative diseases [35] . Furthermore, an association of more rapid disease progression for PD patients with increased Hcy levels [6] and an association of Hcy with the progression of mild cognitive impairment to dementia have been shown [19] . Hcy is also elevated in patients with manifest Alzheimer's disease [9] .…”
Section: Discussionmentioning
confidence: 98%
“…Elevated levels of Hcy correlate with cognitive impairment and finally with dementia [19] . Additionally, a relationship between Hcy and brain atrophy in elderly individuals has been found [20] .…”
mentioning
confidence: 99%
“…Early diagnosis and treatment can improve outcomes but cannot prevent all complications of CblC disease (Rosenblatt et al 1997;Andersson et al 1999;Boxer et al 2005;Smith et al 2006;Thauvin-Robinet et al 2007;Martinelli et al 2011;Aleman et al 2014). Early therapy may be particularly beneficial for late-onset patients, as it can be started prior to the development of any organ damage .…”
Section: Discussionmentioning
confidence: 99%